Therapies from Fucoidan: An Update - Janet Helen Fitton; Damien N. Stringer; Samuel S. Karpiniec (Marine Drugs, 2015)
Fucoidans are a class of sulfated fucose-rich polysaccharides found in brown marine algae and echinoderms. Fucoidans have an attractive array of bioactivities and potential applications including immune modulation, cancer inhibition, and pathogen inhibition. Research into fucoidan has continued to gain pace over the last few years and point towards potential therapeutic or adjunct roles. The source, extraction, characterization and detection of fucoidan is discussed.